An 18-month follow-up investigation of motor coordination and working memory in primary school children - Rigoli, Daniela; Piek, Jan Patricia; Kane, Robert; Whillier, A.; Baxter, C.; Wilson, P. (Elsevier BV; North Holland, 2013)
The aim of the current study was to examine the relationship between motor coordination and visual working memory in children aged 5–11 years. Participants were 18 children with movement difficulty and 41 control children, assessed at baseline and following an 18-month time period. The McCarron Assessment of Neuromuscular Development provided a measure of motor skills and the CogState One-Back task was used to assess visual working memory. Multi-level mixed effects linear regressions were used to assess the relationship between fine motor skills, gross motor skills, and visual working memory. The results revealed that for children with movement difficulty, better fine motor skills at baseline significantly predicted greater One-Back accuracy and greater (i.e., faster) speed at 18-month follow-up. Conversely, fine motor skills at baseline did not predict One-Back accuracy and speed for control children. However, for both groups, greater One-Back accuracy at baseline predicted better fine and gross motor skills at follow-up. These findings have important implications for the assessment and treatment of children referred for motor difficulties and/or working memory difficulties.